INVESTIGATING STUDENT-TEACHER RATIO AS A FACTOR IN READING PERFORMANCE: THE CASE OF THE PHILIPPINES - Inero Ancho; Aljon Galang; Aaron Dela Cruz; Ria Dela Cruz (ETERNAL (English, Teaching, Learning and Research Journal), 2021)
This paper attempts to investigate the student-teacher ratio of various Southeast Asian nations and each country’s reading performance through the lens of the Programme for International Student Assessment (PISA) scores. This paper employed a purely secondary analysis using data available online. The first phase of the research involved revisiting online documents about the student-teacher ratio in the classroom among selected Southeast Asian nations. In the second phase, reading test scores presented in this study are sourced from PISA. The last phase is the comparison and contrast of the data through a tabular presentation. Findings reveal that the countries with a ratio having the least number of students per teacher ranked higher compared with those with a nation having the greatest number of students per teacher. Singapore, Malaysia, and Brunei Darussalam with a ratio ranging from 8 to 11.6 per teacher scored 408-549 points in the PISA Reading Test while Thailand, Indonesia, and the Philippines with a ratio ranging from 15 to 36 students per teacher scored 340-393 points. It is undeniable that the student population in the classroom positively impacts the teaching and learning processes, particularly in reading as contextualized in this study. The government should recognize the dire need for schools to be provided with appropriate funds to sustain the public education system. Careful analysis of the presented data shows the connection between student-teacher ratio and reading performance as manifested by test scores. It is undeniable that the student population in the classroom positively impacts the teaching and learning processes, particularly in reading as contextualized in this study.